[tex] | 2x - 1 | = | 2x + 3 | [/tex]
[tex] | 2x - 1 | - | 2x + 3 | = 0 [/tex]
+; Nếu [tex] x \geq 0,5[/tex] thì [tex] | 2x - 1 | = 2x - 1 [/tex] và [tex] | 2x + 3 | = 2x + 3 [/tex]
[tex] | 2x - 1 | - | 2x + 3 | = 0 [/tex]
[tex] 2x - 1 - ( 2x + 3 ) = 0 [/tex]
[tex] 2x - 1 - 2x - 3 = 0 [/tex]
[tex] -4 = 0 [/tex] ( Vô lý )
+; Nếu [tex] -1,5 \leq x < 0,5 [/tex] thì [tex] | 2x - 1 | = 1 - 2x[/tex] và [tex] | 2x + 3 | = 2x + 3 [/tex]
[tex] | 2x - 1 | - | 2x + 3 | = 0 [/tex]
[tex] 1 - 2x - ( 2x + 3 ) = 0 [/tex]
[tex] 1 - 2x - 2x - 3 = 0 [/tex]
[tex] -4x - 2 = 0 [/tex]
[tex] -4x = 2 [/tex]
[tex] x = -0,5 [/tex] ( không hợp lý vì ta đang xét trường hợp [tex] -1,5 \leq x < 0,5 [/tex]
)
+; Nếu [tex] x < -1,5 [/tex] thì [tex] | 2x - 1 | = 1 - 2x [/tex] và [tex] | 2x + 3 | = -2x - 3 [/tex]
[tex] | 2x - 1 | - | 2x + 3 | = 0 [/tex]
[tex] 1 - 2x - ( -2x - 3 ) = 0 [/tex]
[tex] 1 - 2x + 2x + 3 = 0 [/tex]
[tex] 4 = 0 [/tex] ( vô lý )
nhưng tui lại tìm ra kết quả -0,5 là hợp lý, không bít sai ở đâu nhỉ